Investigation of PMSE dependence on high energy particle precipitation during their simultaneous occurrence. Issue 1 (1st January 2019) - Rauf, Abdur; Li, Hailong; Ullah, Safi; Meng, Lin; Wang, Bin; Wang, Maoyan
Abstract: This paper is based on the observations of Polar Mesosphere Summer Echoes (PMSE) with the EISCAT VHF 224 MHz radar during the summer month 08–12 July 2013. The effect of high energy particle precipitation on PMSE intensity, particularly during their simultaneous occurrence for longer time interval (longer than or equal to 3-h) has been investigated. The correlation between the two phenomena has been computed using the Spearman rank and Pearson linear correlation coefficient. The variations in high energy particle precipitation reaching down to altitude of 91 km and PMSE intensity in the altitude range of 80–90 km are positively correlated. The electron density irregularity due to ionization caused by precipitating particles might be one of the possible reasons for this positive correlation. Moreover, some other background parameters i.e. K -indices (proxy of high energy particle precipitation) and electron fluxes during the simultaneous occurrence of the two phenomena also support one of the possible reasons given for explanation of the observed positive correlation. The X-rays and proton fluxes have no noticeable effect on PMSE echoes in this study.